Comparison of Allegory Symbols in O Novel by Eka Kurniawan and Animal Farm by George Orwell - Mazro'atul Islakhiyah; Suyatno -; Suharmono Kasiyun (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2020)
This study aims to examine the comparison of allegorical symbols in O's novel by Eka Kurniawan and Animal Farm by George Orwell, which includes comparison of symbolic shapes and their meanings. This study was a qualitative research with a comparative literary approach. This data were in the forms of allegory symbols, meaning symbols in the form of words, sentences and paragraphs in both novels. Data sources used were two novels entitled O and Animal Farm, as well as other supporting books. The results of this study indicate that there are similarities and differences in terms of the shape and meaning of symbols in both novels. The shape of the animal symbol is the form that dominates both novels. Based on the meaning, both novels the same describe the state of a country. These similarities and differences are based on the basis of affinity in comparable literature.